Causes and effects of tax evasion in Ghana - Kumi-Dumor, Emmanuel Earl (2022)
The incidence of tax evasion/avoidance has become one of the major challenges affecting revenue generation in many countries, especially in developing and emerging economies like Ghana. This study aims to examine the causes and effects of tax evasion and tax avoidance in the Sekondi-Takoradi Metropolitan Assembly of the Western Region of The Republic of Ghana. The main objectives are: (i) analyse the causes of tax evasion/avoidance; (ii) analyse the effects of tax evasion/avoidance, according to the point of view of small business owners. The data was collected using a structured questionnaire. The final sample size is based on 97 taxable persons and businesses. According to our findings, the retail sector is more prone to tax evasion; females behave differently from males. In relation to cause and effects, education and marital status are the main differences, as stated by the respondents’ opinion.